An improved automatic MPI code generation algorithm for parallelizing compilation - Yangxia Xiang; Caisen Chen; Hongyan Wang; Zeyun Zhou (2017 IEEE 2nd Advanced Information Technology, Electronic and Automation Control Conference (IAEAC), 2017)
Open64 is an open source compiler with powerful analysis and widely used as a research and commercial development platform. However, it has not been designed and developed to realize MPI parallelization. There are many contributions in the paper. Firstly, the Open64 compiler infrastructure is showed. Secondly, the location of MPI code generation in the Open64 compiler architecture is analyzed. Thirdly, an Open64-based automatic generation algorithm for MPI code is presented. By the experiments of testing the NPB benchmarks, the results show that the approach not only has a high rate of parallel transformation, but also can produce correct MPI parallel programs.